2016
DOI: 10.1007/s11262-016-1394-y
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic study-based hemagglutinin (HA) gene of highly pathogenic avian influenza virus (H5N1) detected from backyard chickens in Iran, 2015

Abstract: Highly pathogenic avian influenza (HPAI) viruses of the H5N1 subtype have been diversified into multiple phylogenetic clades over the past decade and are highly genetically variable. In June 2015, one outbreak of HPAI H5N1 in backyard chickens was reported in the Nogardan village of the Mazandaran Province. Tracheal tissues were taken from the dead domestic chickens (n = 10) and processed for RT-PCR. The positive samples (n = 10) were characterized as HPAI H5N1 by sequencing analysis for the hemagglutinin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The following clades were detected between 2013 and 2017 (Smith et al, 2015;Liu et al, 2016;Marinova-Petkova et al, 2016a;Bhat et al, 2017;El Romeh et al, 2017;Ghafouri et al, 2017a;Rashid et al, 2017;Salaheldin et al, 2017;Shittu et al, 2017 (Torchetti et al, 2015). The following clades were detected between 2013 and 2017 (Smith et al, 2015;Liu et al, 2016;Marinova-Petkova et al, 2016a;Bhat et al, 2017;El Romeh et al, 2017;Ghafouri et al, 2017a;Rashid et al, 2017;Salaheldin et al, 2017;Shittu et al, 2017 (Torchetti et al, 2015).…”
Section: Genetic Characterisationmentioning
confidence: 97%
See 1 more Smart Citation
“…The following clades were detected between 2013 and 2017 (Smith et al, 2015;Liu et al, 2016;Marinova-Petkova et al, 2016a;Bhat et al, 2017;El Romeh et al, 2017;Ghafouri et al, 2017a;Rashid et al, 2017;Salaheldin et al, 2017;Shittu et al, 2017 (Torchetti et al, 2015). The following clades were detected between 2013 and 2017 (Smith et al, 2015;Liu et al, 2016;Marinova-Petkova et al, 2016a;Bhat et al, 2017;El Romeh et al, 2017;Ghafouri et al, 2017a;Rashid et al, 2017;Salaheldin et al, 2017;Shittu et al, 2017 (Torchetti et al, 2015).…”
Section: Genetic Characterisationmentioning
confidence: 97%
“…Since the first detection of Gs/Gd/96 'Guangdong' lineage of A(H5N1) HPAIV in 1996, the HA of the virus has undergone an extensive evolution with the continuous emergence (and disappearance) of multiple genetic clades. The following clades were detected between 2013 and 2017 (Smith et al, 2015;Liu et al, 2016;Marinova-Petkova et al, 2016a;Bhat et al, 2017;El Romeh et al, 2017;Ghafouri et al, 2017a;Rashid et al, 2017;Salaheldin et al, 2017;Shittu et al, 2017 (Torchetti et al, 2015).…”
Section: Genetic Characterisationmentioning
confidence: 99%
“…Here too, migratory birds generally enter the EU during autumn migration, although large-scale movements from countries further to the east may also occur during cold spells. HPAIV so far detected in birds from this route mainly belong to the 2.3.2.1c clade (Marinova-Petkova et al, 2012;Alkhamis et al, 2013), often originating from Central Asia (Bi et al, 2015(Bi et al, , 2016Naguib et al, 2015;Marchenko et al, 2016;Tosh et al, 2016;Ghafouri et al, 2017);…”
Section: Entry Routesmentioning
confidence: 99%
“…Here too, migratory birds generally enter the EU during autumn migration, although large‐scale movements from countries further to the east may also occur during cold spells. HPAIV so far detected in birds from this route mainly belong to the 2.3.2.1c clade (Marinova‐Petkova et al., ; Alkhamis et al., ), often originating from Central Asia (Bi et al., , ; Naguib et al., ; Marchenko et al., ; Tosh et al., ; Ghafouri et al., ); the southern route (S), via the EU border from the southern border of Turkey to the northern border of Portugal. Entry via this route is, as opposed to the above, mostly occurring during spring, as birds migrate back from their African wintering grounds.…”
Section: Assessmentmentioning
confidence: 99%
“…In some countries, backyard poultry farming has been found to be associated with outbreaks of Newcastle disease, salmonella infections and avian influenza [11][12][13][14]. Similarly, Turkey experienced outbreaks of highly pathogenic avian influenza (H5N1) in 2006, and it was reported that the transmission of the H5N1 virus from wild animals to domestic animals in Turkey was closely connected to backyard poultry farming [15].…”
Section: Introductionmentioning
confidence: 99%